Optimization of the sodium picrate method effects of parameter variations in total cyanide content determination of cassava (Manihot esculenta crantz) roots. - Sansaet, Ivan Dave C.
Four parameters: 1) mass of sample, 2) volume of incubation vessel, 3) volume of phosphate buffer solution, and 4) incubation time of sodium picrate method were varied to investigate their effects on the total cyanide content of the Cassava (Manihot esculenta Crantz) roots. Sodium picrate method by Topor (2015) was set as the standard method. Three levels of each parameter were identified and crossed to one another to investigate their interactions. The data was analyzed using 4-way ANOVA. Mass of sample, volume of phosphate buffer solution, and incubation time were determined significant parameters of sodium picrate method. Using 0.0500-g mass of sample, 20-mL incubation time, 0.5-mL buffer solution, and 16-hour incubation could maximize the HCN liberation and reaction, yielding mean cyanide content of 83.152 ppm. Mass of sample-volume of buffer solution, mass sample-incubation time, and mass of sample-volume of buffer solution-incubation time interactions were also identified to be significant. These findings could be the basis for the improvement of the protocol in the determination of total cyanide content of cassava roots.